2020
DOI: 10.1186/s12917-020-02583-1
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and fecal metabolites in captive and wild North China leopard (Panthera pardus japonensis) by comparsion using 16 s rRNA gene sequencing and LC/MS-based metabolomics

Abstract: Background Gut microbes significantly contribute to nutrient digestion and absorption, intestinal health and immunity, and are essential for the survival and environmental adaptation of wild animals. However, there are few studies on the gut microbiota of captive and wild North China leopard (Panthera pardus japonensis). Results A total of 10 mainly bacterial phyla were identified in the fecal microbiota of North China leopard, Lachn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The effect of enzymes produced by the intestinal microbiome on the metabolism of steroids is well known, and studies have shown that the quality and quantity of metabolites are influenced by intestinal bacteria [ 2 , 12 , 17 ]. The effect of bacteria continues in faecal material after defecation and can have effects on the stability of metabolites [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of enzymes produced by the intestinal microbiome on the metabolism of steroids is well known, and studies have shown that the quality and quantity of metabolites are influenced by intestinal bacteria [ 2 , 12 , 17 ]. The effect of bacteria continues in faecal material after defecation and can have effects on the stability of metabolites [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we froze the samples for storage to avoid further changes of FCM levels. Whereas some studies reported an increase in FCM values after simulated or natural wet weather [ 12 , 22 ], others could not identify changes after water was poured onto the samples [ 19 ]. It was interesting to notice that, in our study, despite the physical change in the pellets due to rain in treatment E, there was no significant variation in the adjusted FCM values measured by the 50c EIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, metabolomic studies of fecal samples have found that metabolic phenotypic changes are associated with gut microbiota changes in the development of diseases [ 40 ]. Through fecal analysis, we compared the metabolic pathways, metabolite types, and the relationship between the microbial community and metabolites between the 5-ASA and DSS groups and the CSWE(H) and DSS groups.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, metabolomic studies of fecal samples have found that metabolic phenotypic changes are associated with gut microbiota changes in the development of diseases [40].…”
Section: Discussionmentioning
confidence: 99%